DESIGN OF MICRO CLIMATE DATA ACQUISITION SYSTEM BASED MICROCONTROLLER ARDUINO ON GREEN HOUSE - Putri, Heidi Yanti Anggraeni (The University of Lampung, 2015)
Micro climate (temperature, humidity and solar’s intensity) plays animportant role on growth anddevelopment ofplants.However,it is difficult to obtainthemicro climate data continuously. An automatic data acquisition systemis a such promising soluticts to this problem. The aimof this researchwas tomakemicro climate data acquisitionsystem in real time and save it into computer’smemory. It consists of five stages included system design, sensorcalibration, systemanalysis,data acquisition, and systemtesting. MicrocontrollerArduinoUNO based acquisitionsystem designed has several inputs, i.e. three DHT11 temperature and humidity sensors and a light dependentresistor (LDR). The outputs of this system were displayed on the LCD, and on the PC using virtual instrumentengineeringworkbench (LabVIEW) softwere, then the data were stored inMicrosoft Excel. The average error oftemperature sensor for eachDHT11 comparedwith alcohol thermometer readingwas 0,8oC forbothDHT11-(a)and -(b), and 0,2 oC DHT11-(c). The average error of relative humidity (RH) sensor for each DHT11 comparedwith Cole Palmer’s termocopel was 14,63%for DHT11-(a), 16,63%for DHT11-(b), and 11,13%for DHT11-(c).The light intensity can be successfullymeasured using LDR voltage with an error of ± 8.98%and R of 0.9926.Keywords:Data acquisition system, greenhouse,LabVIEW,micro climate,microcontroller ArduinoUNO